Modification of tensile and impact properties of crosslinked rubber toughened nanocomposites via electron beam irradiation - Jamal, N.A.; Anuar, Hazleen; Razak, S.B.A. (AM Publishers Corporation Canada, 2011)
Enhancing the tensile and impact properties of high density polyethylene (HDPE)/ethylene propylene diene monomer (EPDM) matrix is the main target of developing nanocomposite. The nanocomposite system was first prepared via melt intercalation method with different organophilic montmorillonite (OMMT) loadings. Electron beam (EB) irradiation was applied as a crosslinking agent for modification of tensile and impact properties of HDPE/EPDM matrix and HDPE/EPDM filled OMMT systems. The effectiveness of EB irradiation technique were then compared with control one (uncrosslinked system) and analyzed based on the tensile and impact tests as well as morphological xamination. The tensile and impact tests revealed that control and EB irradiated systems had attained the optimum tensile and impact properties at 4 vol% OMMT content. EB irradiated system at dose rate of 100 kGy showed excellent in tensile and impact properties with the highest rosslinking degree which were proved by gel content analysis. X-ray diffraction (XRD) analysis confirmed the existence of delamination structure with EB irradiation technique based on the disappearance of characteristic peak. The degree of delamination was further investigated by transmission electron microscope (TEM).